The untold story - Cogman, Genevieve (The invisible library novel, 2021)
"Time-traveling Librarian spy Irene has faced unimaginable challenges across a multitude of worlds, but to keep her friends safe, Irene will have to do what has never been attempted and cut through the tangled web of power at the heart of the Library. Irene is trying to learn the truth about Alberich-and the possibility that he is her father. When the Library orders her to kill him, and then Alberich himself offers to sign a truce, she has to discover why he originally betrayed the Library. With her allies endangered and her strongest loyalties under threat, she will have to trace his past across multiple worlds and into the depths of mythology and folklore, to find the truth and uncover why the Library was first created"--